Controllable Nano-Crystallization in Fluoroborosilicate Glass Ceramics for Broadband Visible Photoluminescence - Yuanhang Xiang; Yi Long; Peiying Cen; Sirang Liu; Zaijin Fang; Renjie Jiao (Nanomaterials)
A transparent fluoroborosilicate glass ceramic was designed for the controllable precipitation of fluoride nanocrystals and to greatly enhance the photoluminescence of active ions. Through the introduction of B2O3 into fluorosilicate glass, the melting temperature was decreased from 1400 to 1050 °C, and the abnormal crystallization in the fabrication process of fluorosilicate glass was avoided. More importantly, the controlled crystallizations of KZnF3 and KYb3F10 in fluoroborosilicate glass ceramics enhanced the emission of Mn2+ and Mn2+–Yb3+ dimers by 6.7 and 54 times, respectively. Moreover, the upconversion emission color of glass ceramic could be modulated from yellow to white and blue by adjusting the Yb3+ concentration. The well-designed glass ceramic is a novel and significant compound to simultaneously provide efficiently coordinated sites for transition metal and rare earth ions. More importantly, the design strategy opens a new way for engineering high-quality oxy-fluoride glass ceramics with properties of excellent stability, controllable nano-crystallization and high-efficiency photoluminescence.